Recruitment and Selection in China: an application to the case of Lenovo - Chen, Hui'an (2006)
Although more and more organizations in China are realizing the importance of Human Resource Management, recruitment and Selection have still been paid little attention. Talent has always been a crucial elements for any organizations success. It is always said that the most important assets in the 21st Century are talents. Therefore, in order to attract, recruit and select top talents, effective recruitment and selection processes are very important steps to perform these tasks. However, under many influences, especially the labour market, culture and political system, most Chinese organizations are still adopting simple recruitment and selection processes. For instance, most organizations in China still use unstructured interviews as the main selection method to select candidates, which are proved to have very low validity and reliability. This study intended to address the current knowledge of recruitment and selection processes in China, and apply these theories and practices to an organization based in China.